Sharing Session Basic of MSME Packaging in Community Services for Business Sustainability - Azmy, Ahmad (Jurnal Pengabdian Pada Masyarakat, 2024)
The sharing session program is carried out as a form of implementing the Tridharma of Higher Education. Focus training by sharing knowledge about product packaging with MSMEs. MSME actors are trained by the South Jakarta MSME Community with a total of 28 participants. The majority of participants came from the culinary sector, including regional foods, cakes and dry chips. This program starts from the planning, implementation and evaluation processes and can be carried out smoothly. At the end of the sharing session, participants filled out an evaluation questionnaire. The evaluation aspect is assessed on the components of the facilities, materials and expectations of the training participants. Most were considered satisfied and very satisfied with the implementation of the training program. This event can be continued with a different theme according to the needs of MSME players. Businesses can have high sustainability by forming consumer loyalty. The product or service being sold can always be remembered by the target market.